Ureteral stent placement and percutaneous nephrostomy in the management of hydronephrosis secondary to cervical cancer. (October 2019) - Tan, Shutao; Tao, Zijia; Bian, Xiaobo; Zhao, Yiqiao; Wang, Ning; Chen, Xiaonan; Wu, Bin
Abstract: Objective: This study aimed to evaluate the efficacy of ureteral stent placement for the treatment of hydronephrosis secondary to cervical cancer and analyze factors that may predict failure of ureteral stent placement and the differences between ureteral stent placement and percutaneous nephrostomy. Study design: Clinical data of patients with cervical cancer complicated with hydronephrosis admitted to our hospital from July 2008 to August 2018 were retrospectively analyzed. To evaluate the efficacy of ureteral stent placement and percutaneous nephrostomy in the management of hydronephrosis secondary to cervical cancer. Results: A total of 89 patients were analyzed. A ureteral stent was successfully placed in 60 patients. Indwelling stent failed in 29 patients, and then percutaneous nephrostomy was performed. Both surgical procedures were safe and effective. There was a significant correlation between the success rate of ureteral stent placement and the degree of hydronephrosis and the length of the ureteral obstruction. There was no significant difference in the incidence of complications following ureteral stent placement and percutaneous nephrostomy, while there were significant differences between the two treatment modalities in terms of surgical time, hospitalization time, and surgical cost. Conclusion: Ureteral stent placement is the preferred method for the treatment of hydronephrosis secondary to cervical cancer. However, in patients with more severe hydronephrosis and ureteral obstruction >3 cm in length, percutaneous nephrostomy may be more appropriate.